Step-by-step Solution

Find the implicit derivative $\frac{d}{dx}\left(y=\frac{y+3}{x-4}\right)$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Step-by-step explanation

Problem to solve:

$\frac{d}{dx}\left(y\right)=\frac{y+3}{x-4}$

Final Answer

We cannot solve this problem. But soon we will!

Problem Analysis

$\frac{d}{dx}\left(y\right)=\frac{y+3}{x-4}$

Related formulas:

4. See formulas

Time to solve it:

~ 0.09 seconds